Analysis of The Impact of Capital Structure and Company Size on Profit Quality, Using Company Age as Control Variable - Sululing, Siswadi (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research aim : This paper aims to empirically determine the effect of capital structure, company size, and company age as control variables on earnings quality in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Design/Method/Approach : This research is a type of quantitative research that uses secondary data in the form of company annual reports. This study used a sample of 14 companies in the food and beverage sub-sector. This paper examines the factors that influence the quality of earnings on the Indonesian stock exchange. This research was conducted at 14 food and beverage sub-sector companies in 2019-2021. Data analysis techniques in this study used regression model selection tests, classical assumption tests, multiple linear regression, and partial hypothesis testing with the SPSS version 22 program. Research Finding : Based on the results of data analysis, the research findings are (1) capital structure has a negative effect on earnings quality, (2) firm size has a positive effect on earnings quality, (3) firm age has no effect on earnings quality. Theoretical contribution/Originality : This paper expands knowledge and investigates the factors that affect earnings quality. Practitionel/Policy implication : - Research limitation : As this paper focuses on one country, the findings may not be generalizable. In addition, the relatively small sample size could be another limitation.